2021
DOI: 10.3390/ijerph18052538
|View full text |Cite
|
Sign up to set email alerts
|

University Students’ Self-Rated Health in Relation to Perceived Acoustic Environment during the COVID-19 Home Quarantine

Abstract: Background: Online education became mandatory for many students during the Coronavirus disease 2019 (COVID-19) pandemic and blurred the distinction between settings where processes of stress and restoration used to take place. The lockdown also likely changed perceptions of the indoor acoustic environment (i.e., soundscape) and raised its importance. In the present study, we seek to understand how indoor soundscape related to university students’ self-rated health in Bulgaria around the time that the country w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 125 publications
2
20
0
1
Order By: Relevance
“…In contrast, soundscapes heavily affected by traffic were described as irritating, unpleasant, disturbing, and disorganized. In that sense, Dzhambov et al (2021) conducted a study to understand how indoor soundscapes related to university students' self-rated health around the time that Bulgaria was under a state of emergency declaration due to the COVID-19 pandemic. They concluded that a restorative environment such as one supplying nature sounds and relatively free of mechanical sounds could contribute to personal coping resources needed to offset stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, soundscapes heavily affected by traffic were described as irritating, unpleasant, disturbing, and disorganized. In that sense, Dzhambov et al (2021) conducted a study to understand how indoor soundscapes related to university students' self-rated health around the time that Bulgaria was under a state of emergency declaration due to the COVID-19 pandemic. They concluded that a restorative environment such as one supplying nature sounds and relatively free of mechanical sounds could contribute to personal coping resources needed to offset stress.…”
Section: Discussionmentioning
confidence: 99%
“…In Bulgaria, Dzhambov et al (2021) conducted a study to understand how indoor soundscapes related to university students' self-rated health around the time that the country was under a state of emergency declaration caused by the COVID-19 pandemic. They found that greater exposure to mechanical sounds was consistently associated with worse self-rated health and that nature sounds correlated with higher restorative quality of the home.…”
Section: Introductionmentioning
confidence: 99%
“…The level of importance of the criterion of choosing a quiet and peaceful place to live did not change between the study periods. Quiet and peaceful places, especially natural green areas, can relieve stress [85], and mechanical noise adversely affects the well-being of students during lockdown [86]. The preference for the residence location was mainly due to evaluating the level of comfort (convenient commuting, peace and quiet), with the relative importance of these criteria reaching 34.5% and 20.4% respectively for DATE(1), and 33.3% and 20.5% for DATE (2).…”
Section: Discussionmentioning
confidence: 99%
“…Human-generated sound levels such as talking and walking, as well as nature sounds such as birdsong, through open windows increased within home environments [154]. Still, greater exposure to mechanical noise during home confinement contributed consistently to a resident's worse self-reported health, whereas nature sounds correlated with greater restorative capacity of the home; however, those dwellers having soundproof windows installed in their homes, and therefore more acoustic comfort, reported better overall wellbeing independently associated [153]. In contrast, where construction/public work and neighbourhood noise was reported to become an annoyance for residents, housing characteristics were an important factor of indoor acoustic environment and complaints during lockdown [164,165].…”
Section: Housing Design and Constructive Characteristics Impact On Environmental Conditionsmentioning
confidence: 99%
“…Residents with access to some environmental affordances at the time of lockdowns experienced better mental health status during COVID-19 (Table 1). Elements included houseplants, home garden access and usage and visibility of greenery and/or blue spaces from the windows [18,[148][149][150][151][152], as well as indoor soundscape prominently coming from nature [153] as mechanical noise like traffic noise reduced [154]. Across several European countries, including France, Germany, Italy, Portugal, Spain, and the UK, as well as New Zealand, US and Mexico, people under lockdown at homes with accessible outdoor spaces and views of nature showed lower symptoms of depression and anxiety [18].…”
Section: Buffering Effect Of Housing Conditions On Resident's Mental Health During Covid-19 Lockdownmentioning
confidence: 99%